An Examination of the Levels and Differences in Organizational Commitment of Full and Part Time Community College Faculty - Duane Akroyd; Deborah Engle (Adult Education Research Conference, 2014)
Despite the widespread employment of part-time faculty in community colleges, there is little known about the commitment levels of these faculty, or how it compares to their full-time counterparts. The purpose of this study was to determine if the levels of affective, continuance, and normative commitment for full-time faculty differed significantly from part-time faculty in North Carolina community colleges? Analysis of variance (ANOVA), found that mean scores of affective, and normative commitment were significantly higher for full-time faculty than part-time faculty.